KEEFEKTIFAN MANFAAT, KEMUDAHAN PENGGUNAAN, DAN KEAMANAN PADA MINAT MENGGUNAKAN E-MONEY DALAM MEMINIMALISIR PENYEBARAN COVID-19 PADA MASYARAKAT DI MASA PANDEMI - Eny Puspita Ningrum (Universitas Mataram, 2022)
This study aims to determine the significance of the effectiveness of the use of e-money on the interest of the community in Takisung Village in using e-money to minimize the spread of Covid-19. In this study, the method used is a quantitative method with a descriptive type of research. In this study, information was obtained from respondents by using questionnaires and for calculations using a research scale, namely the ordinal scale in the form of a scale likert. The sample of this study is the people who live in Takisung Village with the sample criteria being at least 20 years old and using e-money. Sources of data in this study using primary and secondary data sources. Primary data sources were obtained through questionnaires given to 100 respondents, while secondary data sources were obtained from library research. The results of this study indicate that the perception of benefits, ease of use and safety shows a positive direction and significance to the interest in using e-money, as well as the overall results also show that the use ofe-moneyminimize the spread of Covid-19